Gla-rich protein function as an anti-inflammatory agent in monocytes/macrophages: implications for calcification-related chronic inflammatory diseases - Viegas, Carla (2018)
Calcification-related chronic inflammatory diseases are multifactorial pathological processes, involving a complex interplay between inflammation and calcification events in a positive feed-back loop driving disease progression. Gla-rich protein (GRP) is a vitamin K dependent protein (VKDP) shown to function as a calcification inhibitor in cardiovascular and articular tissues, and proposed as an anti-inflammatory agent in chondrocytes and synoviocytes, acting as a new crosstalk factor between these two interconnected events in osteoarthritis. However, a possible function of GRP in the immune system has never been studied. Here we focused our investigation in the involvement of GRP in the cell inflammatory response mechanisms, using a combination of freshly isolated human leucocytes and undifferentiated/differentiated THP-1 cell line. Our results demonstrate that VKDPs such as GRP and matrix gla protein (MGP) are synthesized and gamma-carboxylated in the majority of human immune system cells either involved in innate or adaptive immune responses. Stimulation of THP-1 monocytes/macrophages with LPS or hydroxyapatite (HA) up-regulated GRP expression, and treatments with GRP or GRP-coated basic calcium phosphate crystals resulted in the down-regulation of mediators of inflammation and inflammatory cytokines, independently of the protein gamma-carboxylation status. Moreover, overexpression of GRP in THP-1 cells rescued the inflammation induced by LPS and HA, by down-regulation of the proinflammatory cytokines TNF alpha, IL-1 beta and NFkB. Interestingly, GRP was detected at protein and mRNA levels in extracellular vesicles released by macrophages, which may act as vehicles for extracellular trafficking and release. Our data indicate GRP as an endogenous mediator of inflammatory responses acting as an anti-inflammatory agent in monocytes/macrophages. We propose that in a context of chronic inflammation and calcification-related pathologies, GRP might act as a novel molecular mediator linking inflammation and calcification events, with potential therapeutic application.